Pervyi uchitel' - Mikhalkov-Konchalovskii, Andrei (Soviet Union : Mosfilm ; Kirgizfilm, 1965)
Soviet Kirgizia, the first years of the Soviet regime. A young tecaher Dyushein has just come to a little country village. He is a teacher, sent by the Communist Party to teach the ignorant masses. Although the children accept him, many adults barely tolerate his presence since they see him as a threat to their way of doing things. The movie shows Diuishen, propelled by his ideological fanaticism, learning to be human and the townsfolk, equally fanatic in their desire to keep the outside world at bay. Soon his love to a young Altynai breaks the traditions leading to dramatic events.
Keywords: Fiction films